(untitled) (Medico Legal Update, 2020)
This research aimed to reveal the potency of green tea (Camellia sinensis) as immunomodulator, anti apoptosis agent and anti pyroptosis agent in Systemic Lupus Erythematosus.. The rest samples was downloaded from KNAPSACK Database. Biological activity prediction was conducted by PASS SERVER. Molecular Docking analysis was performed by Autodock Vina in PyRx software v.0.9.3. Complex docking was analyzed and visualized using Discovery Studio Software. The result showed that Camellia sinensis has the main potency as immunomodulatory, antioxidant and anti-inflammation. The highest activity of this herbal is antioxidant. There are few bioactive that have role as immunomodulator. The result of molecular docking can explain the mechanism of active compound as anti-apoptosis and anti-pyroptosis. Docking result showed that Theaflavin has the highest affinity to both activities. It can be concluded that bioactive from Camelia sinensis is promising for curing Systemic Lupus Erythematosus by acting as antioxidant and inhibit apoptosis and pyroptosis mechanism.